MENINGKATKAN PRESTASI BELAJAR KIMIA MELALUI PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING PADA MATERI MINYAK BUMI SISWA KELAS XI MIA 3 MAN 1 ACEH BESAR - Thursina Thursina (UIN AR-RANIRY, 2017)
Chemistry teaches student to understand the chemistry concepts and the interrelated applications in everyday life as well as for technological advancement, its namely student using the centered learning (student centered). This study raises the problem whether through cooperative learning of Snowball Throwing type can improve student learning outcomes on Hydrocarbon material and how student activity in learning activities. This research was a classroom action research. Research settings consist of place, time research and action reasearch cycle, which became the subject of research was the students of class XI MIA 3 which consisted of 31 students. To know the influence of the application of cooperative learning model of Snowball Throwing type was by observation on student activity from questionnaire. Data obtained from the observation of the activity of students and teachers reached the categories of good and very good based on predetermined criteria. From the first cycle the test result obtained 67,74%, in second cycle the test result increased by 87,1%, and the final test was obtained 96,77%. Based on the results of this study, it can be concluded that the application of cooperative learning model of Snowball Throwing type in Hydrocarbon material of class XI MIA 3 MAN 1 Aceh Besar can improve the learning result and the student activity.